INVESTIGASI KEGAGALAN POMPA SENTRIFUGALTIPE KSB KAPASITAS 235 M3/H TERHADAP CHILLER TRIP DI PT. PHPO BELAWAN MEDAN DENGAN METODE RELIABILITY CENTERED MAINTENANCE (RCM) - Siahaan, Enzo W. B; Sitanggang, Hodmiantua; Manalu, Citra Satria (Universitas Quality, 2023)
In the Crude Palm Oil (CPO) processing industry, it becomes a better quality product such as RBDPO (Refined Bleached Deodorized Palm Oil). RBDPO becomes RBDPO Olein and RBDPO Stearin. The more often the pump is used, the lower the performance of the pump's ability, which has an impact on the replacement of components in the pump engine. Symptoms that often occur in pumps are leaks in the packing both the Mechanical Seals and Rubber Couplings or damage to components such as bearings or impellers. The maintenance system at this company pays little attention to machine notifications, if a failure occurs it will only replace the damaged component without regard to the condition of the machine for the future usage process. Therefore, in this study, a failure analysis was carried out on centrifugal pumps using the RCM (Reliability Centered Maintenance) method which includes making a malfunction which then looks for the damage mode, the cause of the damage will be determined so that the effect of the damage on the pump performance can be analyzed. There are several stages in the preparation carried out. The final results obtained from the RCM method, namely the preparation of Failure Mode Effect Analysis, obtained the highest failure rate, namely Mechanical Seals (Mech seals) with a value of 96 and Rubber Couplings with a value of 84, so that intensive maintenance is needed which is expected to increase the operating life of the pump. From the results of the fault tree analysis, the reliability value is below 50%, which means that it has poor maintenance.